Some Observations Concerning the Length of Vowels and Diphthongs in the Vidiškiai Dialect - Markevičienė, Žaneta; Markevičius, Valdimantas (Kalbotyra, 1995)
Lithuanian dialectologists hold an opinion that in the dialects of Eastern Aukštaitians (“highlanders”), covering the areas Širvintos and Panevėžys, the short stressed vowels in the stem become long; thus, the words lìnas “flax” and lýnas “tench”, lùpa “beats, flogs” and lū́pa “lip” sound alike. In order to confirm this fact a computer test was undertaken to measure the length of the vowels i, u, and i., u. in the words lìnas - lýnas, lùpa - lū́pa, etc. Although these words are pronounced in a very similar manner, the experiment proved that the short stressed vowels, having become long, still remain somewhat shorter than the usual long vowels. It also proved that the normally stressed diphthongs ai, au and others are slightly longer than the same diphthongs under the retracted stress.